Effect of cryoprotectant and equilibration temperature on cryopreservation of Lama glama spermatozoa. (25th July 2014) - Carretero, M. I.; Neild, D. M.; Ferrante, A.; Caldevilla, M.; Arraztoa, C. C.; Fumuso, F. G.; Giuliano, S. M.
Summary The aim of this study was to determine the effect of two equilibration temperatures (5 °C and room temperature) and two cryoprotectants (glycerol and dimethylformamide, both at 7%) on llama sperm cryopreservation. Llama ejaculates were divided into four aliquots. A lactose‐EDTA‐egg yolk (LEEY) extender with either 7% glycerol (LEEY‐G) or 7% dimethylformamide (LEEY‐DMF) was added to two of the aliquots, which were equilibrated for 20 min at room temperature and subsequently frozen. The other two aliquots were extended in LEEY, cooled to 5 °C, then LEEY‐G or LEEY‐DMF was added, equilibrated for 20 min at 5 °C and frozen. No significant differences (P > 0.05) were observed in membrane function and chromatin condensation between any of the freeze–thawing protocols. Post‐thaw motility was greater (P < 0.05) in LEEY‐DMF than LEEY‐G. DNA fragmentation was not different between raw and frozen semen with LEEY‐DMF but was high in all samples with glycerol. Our results indicate that 7% glycerol would be detrimental for llama spermatozoa, but further studies are needed to evaluate effectiveness if used at lower concentrations. Dimethylformamide preserved motility and DNA integrity of frozen–thawed llama spermatozoa and could be used to replace glycerol at the concentrations used in this study.